2010
DOI: 10.1097/qai.0b013e3181bcdae0
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 Incidence Rates and Risk Factors in Agricultural Workers and Dependents in Rural Kenya: 36-Month Follow-Up of the Kericho HIV Cohort Study

Abstract: HIV-1 incidence rates were relatively low in adult plantation workers and dependents in rural Kenya. Cohorts including higher risk populations (eg, commercial sex workers) warrant consideration for regional HIV preventive vaccine trials. Even low incidence, well-described cohorts generate valuable epidemiological clinical trial data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 19 publications
3
19
1
Order By: Relevance
“…Ten studies provide data on men, four of which provide data exclusively on young men. Three studies provided measures of association that were not sex disaggregated [1618]. Overall, 14 studies (17 papers) were cross-sectional or repeated cross-sectional and provide HIV prevalence measures, whereas two cohort studies provided HIV incidence measures.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ten studies provide data on men, four of which provide data exclusively on young men. Three studies provided measures of association that were not sex disaggregated [1618]. Overall, 14 studies (17 papers) were cross-sectional or repeated cross-sectional and provide HIV prevalence measures, whereas two cohort studies provided HIV incidence measures.…”
Section: Resultsmentioning
confidence: 99%
“…Six of the studies drew from a more nuanced definition of transactional sex (sex motivated by material gain/gifts/money) that better distinguishes the practice from sex work [9,10,1922,24,27,28]. Seven studies used a conventional measurement approach, asking about “sex in exchange for gifts or money” [18,23,25,2932], and another two studies did not clearly state their measurement approach, but described transactional sex as distinct from sex work in the text of the article [16,17]. We included one study that measured transactional sex as “ever had sex for money” [26].…”
Section: Resultsmentioning
confidence: 99%
“…All study types were included (e.g., crosssectional, case-control, and cohort) irrespective of the measure of alcohol use employed, as long as a "no-use" referent was available for comparison. Five additional studies were identified by the updated literature review (Adoga et al, 2009;Kalichman, Cain, & Simbayi, 2010;Norris, Kitali, & Worby, 2009;Shaffer et al, 2010;Williams et al, 2009) bringing the total number of studies included in this meta-analysis to 35 (see Table 3). …”
Section: Methods Literature Reviewmentioning
confidence: 99%
“…There were a few notable exceptions: (1) Ayisi et al (2000) reported adjusted and unadjusted risk ratios, (2) Talbot et al (2002) reported adjusted and unadjusted prevalence ORs, and (3) all but two of the cohort studies (Allen et al, 1992;Kalichman et al, 2010) provided rate ratios or data for calculation of a rate ratio (Kapiga et al, 1998;Shaffer et al, 2010;Zablotska et al, 2006Zablotska et al, , 2009. In these instances, the measure of association reported by the authors was used in order to retain the benefit of adjusted rate/risk ratios, although separate analyses were conducted based on study design (e.g., case-control vs. cohort studies).…”
Section: Data Abstractionmentioning
confidence: 99%
“…One population is persons with multiple partners, including sex workers [41][42][43][44][45][46] and MSM in which incidence ranges as high as 8-10 per 100 person years [47,48]. The other is married or cohabiting couples in which one partner is HIV positive and one is HIV negative, who are at high risk even after counseling and condom provision, a type of cohort that has contributed enormously to our understanding of heterosexual transmission as well as the course of HIV infection, with incidence in the range of 2-7 per 100 person years and very high rates of follow-up [49][50][51].…”
Section: Human Efficacy Trials: Considerations Relating To Populationsmentioning
confidence: 99%